The value of systemic inflammatory response index in evaluating the prognosis of postoperative patients with stage II colon cancer - Yong Wang; Longlong Ding; Lingyan Ji; Zhao Yan (BMC Gastroenterology)
Abstract Background Exploring the prognostic value of systemic inflammatory response index (SIRI) for 3-year disease-free survival (DFS) in stage II colon cancer patients after radical surgery. Methods A retrospective analysis was conducted on 87 patients with stage II colon cancer. Patients were divided by 3-year DFS status: poor prognosis group (DFS event; n = 28) vs. good prognosis group (event-free; n = 59). Univariate analysis and multivariate Cox regression analysis were performed to identify the influencing factors on postoperative prognosis of stage II colon cancer patients. Receiver operating characteristic (ROC) curve was used to evaluate the predictive value of various influencing factors on postoperative prognosis of stage II colon cancer patients. Kaplan-Meier method and Log-rank test were used to compare survival differences among patients with different SIRI levels. Results One week before surgery, the neutrophil to lymphocyte ratio (NLR) level in the poor prognosis group was significantly lower (P < 0.05). The levels of SIRI, carcinoembryonic antigen (CEA), carbohydrate antigen 19 − 9 (CA19-9), carbohydrate antigen 125 (CA125), and carbohydrate antigen 72 − 4 (CA72-4) in the poor prognosis group were significantly higher (P < 0.05). NLR, SIRI, CEA, CA19-9, CA125, and CA72-4 were all independent risk factors for the prognosis of postoperative patients with stage II colon cancer. The area under the curve (AUC) for predicting patient prognosis using NLR, SIRI, CEA, CA19-9, CA125, and CA72-4 were 0.726, 0.828, 0.693, 0.741, 0.706, and 0.605, respectively. The optimal cutoff value for SIRI was 1.41, with a sensitivity of 0.67 and a specificity of 0.93. There was a significant difference in the 3-year disease-free survival rate between stage II colon cancer patients with SIRI ≥ 1.41 and SIRI < 1.41 after surgery (P < 0.05). Conclusion Preoperative SIRI predicts early recurrence risk (3-year DFS) more effectively than traditional biomarkers. DFS was significantly higher in patients with SIRI < 1.41.